Servitium amoris in akkadian, greco-roman, and sanskrit literature - Morales Harley, Roberto (2024)
The paper analyzes the topic of the servitium amoris. The author works with a corpus of 80 passages, taken from Akkadian love poetry (The Faithful Lover, I Shall Be a Slave to You, ca. 2000-1500 BCE), Latin love elegy (Tibullus’ Elegies Propertius’ Elegies, Ovid’s Amores; ca. 50-1 BCE), and Sanskrit love lyric (Bhartṛhari’s Passion, ca. s. IV CE; Amaru’s Hundred Poems, ca. s. VII CE; and Bilhaṇa’s The Fifty Stanzas of a Thief, ca. s. XI CE). The article proposes the possibility of an Akkadian influence in the Greco-Roman version of the topic, as well as the possibility of subsequent influence of the latter in the love poetry in Sanskrit language.